Integrative Health: An Interprofessional Standardized Patient Case for Prelicensure Learners - Josette Rivera; Rosalind de Lisser; Anand Dhruva; Amber Fitzsimmons; Susan Hyde; Sanjay Reddy; Candy Tsourounis; Shelley R. Adler (Association of American Medical Colleges, 2018)
Introduction Integrative health care and complementary medicine are widely used by the U.S. population, yet health professions learners are typically inadequately educated to counsel patients on the use of these approaches. This interprofessional standardized patient exercise (ISPE) provides learners the opportunity to discuss various health care professionals' roles in caring for a patient interested in integrative health strategies, and to collaborate on a care plan. Utilizing this ISPE format aligns with the principles of integrative health as it requires interprofessional collaboration to address the multifaceted needs of patients. Methods The ISPE is approximately three hours in duration, and required of all UCSF, third-year dentistry, physical therapy, and medical students; second-year nurse practitioner students, and fourth-year pharmacy students. Social work, nutrition, and chaplain trainees also participated. Working in interprofessional teams of 4-5 learners, team members discuss case information, interview the standardized patient (SP) individually, jointly formulate a care plan, and, discuss the plan with the SP. The experience is debriefed with a facilitator. Results In 2016-17, 520 learners participated in the ISPE. They agreed that they learned about the roles of other health care professionals (M = 5.24 on a six-point scale, SD = 1.27), and that they would recommend the ISPE to fellow students in their profession (M = 5.25, SD = 1.30). Discussion Students appreciated the ability to observe learners from other health professions interacting with the SP, and how different perspectives and expertise were integrated to create a comprehensive care plan. The exercise can be adapted to accommodate local health professions learners.